About Beethoven, the silence of Hegel (Revista da Tulha, 2019)
The magnitude that music gained as the object of philosophical thought in the nineteenth century is widely recognized. Even composers, once considered artisans, have become influential thinkers after the growth of importance of music in the thinking of great philosophers. Ludwig van Beethoven (1770-1827) stands out as the pioneer of a trend that will culminate in Richard Wagner's relevance to the history of philosophy: In the nineteenth century the most important philosophers will give a certain primacy to aesthetics - including the musical - recently organized as a discipline. This is the case of G. W. F. Hegel (1770-1831), Beethoven's contemporary philosopher most influential. The hypothesis of this study starts from the unrelation between these two important protagonists which in the indicated historical conjuncture is strangely remarkable. Hegel in his many lectures on art and music never refers Beethoven among the many composers he uses as his examples; moreover, it is possible that there are certain veiled censures of poetic-stylistic character developed in his writings, applicable to the music of the German composer. On the other hand although there is no record of Beethoven's comments about his absence in Hegel's philosophy, the hypothesis of this study suggests that the response to the Hegelian program may have occurred in the artistic field, specifically through his Ninth Symphony. Still little explored, the conjunction art-philosophy, taken in the context of the relationship between composers and philosophers, can find here a less noisy preview of the consecrated Nietzsche-Wagner clash. Thus this essay aims to speculate precisely on what emerges from the silence of both actors concerned: what Hegel did not say, and what this silence means; what Beethoven did not expose in written record, responding to the Hegelian silence about himself with a musical work, and the effectiveness of this response.